Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I prove the product rule of limits? I want to prove this but I am stuck while proving it. Please help me. I mean:

$$\lim\limits_{x\to c}\ (f(x)\cdot g(x)) = \left [\lim_{x\to c}\ f(x) \right] \cdot \left [\lim_{x\to c} \ g(x) \right] $$

share|cite|improve this question
Please don't only name the theorem but also state it, otherwise you might get an answer you don't expect. – Listing Nov 30 '11 at 18:28
You should specify whether you're talking about limits of functions or sequences. Useful link:… – Martin Sleziak Nov 30 '11 at 18:28
Where exactly are you stuck? – Listing Nov 30 '11 at 18:47
Hint: $f(x)g(x)-ab=(f(x)-a)g(x)+a(g(x)-b).$ – André Nicolas Nov 30 '11 at 18:51
up vote 4 down vote accepted

HINT $\: $ It's simple if $\rm\:f\to 0\:$ or $\rm\:g\to 0\:.\:$ By linearity we can reduce the general case to a sum of such simple cases as follows. Suppose $\rm\:f\to a,\ g\to b\:.\:$ Then $\rm\ f_0 := f-a \to 0,\ \ g_0 := g-b\to 0\:,\ $ hence

$$\rm f\:g - ab\ = \ (f_0+a)\:(g_0+b) - a\:b\ =\ f_0\ g + a\ g_0\ \to\ 0 $$

since the final term above is a sum of said cases that are simply proved to $\to 0\:.\ $ An analogous proof works also for many other product rules, e.g. for congruences in number theory we have

Congruence Product Rule $\rm\ \ f\equiv a,\ g\equiv b\ \Rightarrow\ f\:g\equiv ab\ \ (mod\ m)$

Proof $\rm\:\ \ m\ |\ f-a,\ g-b\:\ \Rightarrow\:\ m\ |\ (f-a)\ g + a\ (g-b)\ =\ f\:g - ab\quad $ QED

The "simple case" used above is $\rm\ h\equiv 0\ \Rightarrow\ c\:h\equiv 0\ $ i.e. $\rm\ m\ |\ h\ \Rightarrow\ m\ |\ c\:h$

When you study ring theory you will learn that the fundamental algebraic structure at the heart of the above proofs is the notion of an ideal in a ring, or a module over a ring. Namely, above, the elements that $\to 0\:$ or are $\equiv 0$ resp., form a subgroup (i.e. are closed under subtraction) and are further closed under multiplication by an arbitrary ring element ("scaling"). This fundamental linear structure is a ring-theoretic generalization of the structure of a vector space over a field. However, since the scalars need only be a ring (vs. a field), the theory is a bit more complicated, due in large part to the fact that one can no longer always cancel or invert nonzero scalars.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.